Heterologous PrP molecules interfere with accumulation of protease-resistant PrP in scrapie-infected murine neuroblastoma cells. - Priola, S A (1994)
Mutations within a host cellular protein, PrP, have been associated with disease in the transmissible spongiform encephalopathies. Murine neuroblastoma cells persistently infected with mouse scrapie accumulate protease-resistant PrP (PrP-res), the abnormal form of PrP associated with disease in the transmissible spongiform encephalopathies. These cells provide a controlled system in which to study the molecular interactions which are important in the formation of PrP-res. We have expressed recombinant PrP molecules in mouse scrapie-infected murine neuroblastoma cells and assayed the effect of these heterologous PrP genes on the formation and accumulation of PrP-res. The results demonstrate that expression of heterologous PrP molecules which differ from the endogenous PrP by as little as one amino acid can profoundly interfere with the overall accumulation of PrP-res. The data suggest that precise interactions between homologous PrP molecules are important in PrP-res accumulation and that heterologous PrP molecules can block these interactions.